المنظور الاستراتيجي لاستخدام أنموذج بطاقة الأداء المتوازن محاسبيا وأوجه القصور - د. صالح ابراهيم الشعباني (PROSPECTIVE RESEARCHES, 2023)
The balanced scorecard model is a remarkable development in the field of management accounting as a new approach in the evaluation of the performance because it contains financial and non-financial indicators and it is interrelated within a strategic framework based on a relationship of cause and effect. This model works to achieve balance among the indicators pertaining to perspectives (financial, customers, internal processes, learning and growth) into a single report under the umbrella of the company's strategy for achieving the objective of the company. This model has emerged after confirmation of failure of traditional models of performance evaluation, which was based on financial indicators only on historical data therefore; it does not have the future vision of crossing the company's strategy in the long term. On this basis, the balanced scorecard is a general strategic framework to assist the various levels of the company and translate its objectives and strategic plans to the objectives of the process which can be measured accurately with the guidance of individual performance by linking strategy and the functions of the company's vision of working through the four dimensions.